India: retail and consumer - Singhal, Arvind (Henry Stewart Talks, 2009)
Emerging markets, The optimum retail solution?, Overview of India, Rapid economic growth, Growth of organized retail in India, Key growth drivers, The Indian consumer, Changes in the retail landscape, Key impact areas, Opportunities in the retail sector, Challenges